Religiöser Nonkonformismus und frühneuzeitliche Gelehrtenkultur - Vollhardt, Friedrich (Quellen und Darstellungen zur Geschichte des Antitrinitarismus und Sozinianismus in der Frühen Neuzeit., 2014)
This volume elucidates the socio-cultural and political frameworks that shaped the genesis and dissemination of dissident ideas in the world of scholarship during the Early Modern period. It presents a broad range of interdisciplinary research perspectives on religious pluralization.